2002
DOI: 10.1002/hed.10222
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic nuclear organizer regions in nasopharyngeal carcinoma and paraneoplastic epithelia

Abstract: The morphometric analysis of AgNORs reflected cell proliferative activity and histologic differentiation of tumor rather than malignant transformation in different nasopharyngeal epithelia and NPC. AgNOR area and AgNOR area-count ratio are the most valuable features for differential diagnosis of normal, preneoplastic, and cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As found in this study that the mean AgNOR pre-and posttherapy for the WHO type 3 were statistically different in significant level, therefore, in accordance to the research conducted in 70 patients with NPC paraffin specimens, findings the mean AgNOR for WHO type 3 was higher than those in WHO type 2, our result is proven to be reliably supported. (27) The weakness of this research is limited of time, so that only a few samples can be observed until chemoradiotherapy completion.…”
Section: Acknowledgementmentioning
confidence: 99%
“…As found in this study that the mean AgNOR pre-and posttherapy for the WHO type 3 were statistically different in significant level, therefore, in accordance to the research conducted in 70 patients with NPC paraffin specimens, findings the mean AgNOR for WHO type 3 was higher than those in WHO type 2, our result is proven to be reliably supported. (27) The weakness of this research is limited of time, so that only a few samples can be observed until chemoradiotherapy completion.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Analysis of AgNOR counts showed a significant difference between tumor and residual liver tissues of HCC or normal liver (P < 0.001) and this is in agreement with several studies (Shemizu et al, 1995;Siddiqui et al, 1999;Politi et al, 2004). However, Chen et al (2003) revealed that AgNOR area and AgNOR area-count ratio are the most valuable features for differential diagnosis of normal, preneoplastic, and cancer cells. Spolidorio et al (2002) found that the morphometric results were statistically different for normal mucosa, dysplasia, and microinvasive oral carcinoma and they concluded that an increase of NOR activity follows the disease progression and may reflect the degree of cellular proliferation and malignancy.…”
Section: Agnor Count Reflects Dna Ploidy or Proliferative Activitymentioning
confidence: 99%
“…Many studies have clearly brought out the usefulness of AgNOR in squamous cell carcinomas in this regard. [2][3][4] Thus studies have shown that AgNOR values can serve as a useful prognostic parameter and a marker for tumour progression in squamous cell carcinomas [3,4,10,11].…”
Section: Value Of Silver Binding Nucleolar Organiser Regions (Agnor) mentioning
confidence: 99%